High-Efficient Dust Trapping Performance of AES/Polyacrylamide Strengthen Foam Based on the Structure Stability and Dust Wettability - Lu, Xin-Xiao (Langmuir : the ACS journal of surfaces and colloids, 2022)
The atmospheric dust has a great negative impact on the societal harmonious development that starves for an efficient dust suppressant. This paper proposes a novel AES/polyacrylamide strengthen foam (APSF) to improve the dust trapping effectiveness. The APSF structure property and dust suppression capacity are studied and evaluated through the molecular dynamics simulation and experimental tests. The results express that APSF exhibits the stronger structure stability, superior water retention, and slower drainage performance than the traditional water-based foam (WBF). APSF dynamic simulation is studied by the relative concentration, radial distribution function, head group orientation, and mean square displacement. Research shows that APSF introduces water to thicken the hydration layer. The interaction strength between water and surfactant head groups is enhanced by 22.62 and 31.37% in the first and second hydrated water shells. APSF improves the sodium fatty alcohol ether sulfate (AES) orientation and weakens the diffusion of water molecules, which favors the foam stability. APSF exerts a better wettability on the coal dust through the wet settlement and contact angle tests. The APSF liquid film thickness reduces to 58.05 from 64.80 μm that is 3.14 times of WBF according to the foam liquid film decay experiment. Fourier transform infrared (FTIR) spectroscopy analysis indicates that there is an evident reinforcement on the coal surface absorption peak intensity of hydroxyl- and oxygen-containing functional groups treated by APSF. FTIR results are further determined by energy-dispersion spectrum analysis